Determining influences of intraoperative s-ketamine on postoperative delirium and cognitive function: methodology is important - Dan-Feng Wang; Fei Gao; Fu-Shan Xue (Journal of Cardiothoracic Surgery)
Abstract The letter to the editor was written in response to the recent article by Wang et al. “The influence of low-dose s-ketamine on postoperative delirium and cognitive function in older adults undergoing thoracic surgery”, which is published in Journal of Cardiothoracic Surgery. 2024; 19(1):324. This article concludes that intravenous low-dose S-ketamine during thoracic surgery in older patients significantly reduces the incidences of postoperative delirium and cognitive dysfunction, indicating a potential neuroprotective effect of intraoperative low-dose S-ketamine. In view to the retrospective nature of this study and their inconsistent findings with the results of a recent randomized controlled trial performed in patients undergoing non-cardiac thoracic surgery, we believe that several methodological issues and potential confounders in this study deserve further clarification and discussion before accepting their conclusions. Our main concerns include lacking the times and number of delirium monitoring per postoperative day, alone use of the Confusion Assessment Method form for delirium screening, not providing the factors related to the occurrence of postoperative delirium in the ICU stay, and application of a non-standard definition for postoperative cognitive impairment. We believe that clarification of these issues is useful for improving the transparency of their methodology and facilitating the interpretation of their results.